PENGENALAN DAN PELATIHAN OPERASIONAL APLIKASI AKUNTANSI BERBASIS ANDROID DI UMKM ONDOMOHEN PACK - Ninik Mardiana; Rika Puspita Sari; Sumartono; R.Ayu Erni Jusnita; Kusmiyati (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
UMKM Ondomohen Pack, is a micro business engaged in producing packaging made of cardboard whose shape can be ordered according to the wishes of the customer. This PKM is a continuation of the collaboration with UMKM Ondomohen Pack which was held in 2019. This UMKM still needs improvement here and there, so this collaboration is sustainable. This year what the service lecturer team wants to fix is ​​the problem of recording financial bookkeeping which still uses a manual system by recording in a ledger. Therefore the team of community service lecturers will provide an introduction and training to MSME staff on android applications that can be used to handle financial records by utilizing available android applications. The implementation method begins with discussion and observation about what still needs to be fixed on the Ondomohen Pack, then training and mentoring will be held so that workers in charge of financial records understand Android-based accounting operations.